Continuities and ruptures in the education act of the province of Buenos Aires (1875-1995) (2017)
This article follows a historical track of the Education Act of the province of Buenos Aires between its sanction in 1875 and the reforms of 1951 and 1995, in order to answer why the overthrow of the Peronist government in 1955, which is considered – by the actors themselves and the social sciences- as a turning point in the periodization of history of education in Argentina, did not imply the enactment of a new law. For this purpose, they were analyzed various texts of the Education Law that were approved in 1875, 1951 and 1995, the partial amendments, the reform projects that were not sanctioned and the debates in the Buenos Aires legislature that were carried out in this regard. It is observed that the reforms to the law coincided with profound changes in the objects of legislation that occurred within the framework of transformations in the Argentine State. Therefore, it is concluded that it is possible to question the scope of assuming the overthrow of the Peronist government in 1955 as a turning point in the periodization of the History of Education in Argentina.